2018
DOI: 10.1101/361790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fluorescence Multiplexing with Spectral Imaging and Combinatorics

Abstract: Ultraviolet-to-infrared fluorescence is a versatile and accessible assay modality, but is notoriously hard to multiplex due to overlap of wide emission spectra. We present an approach for fluorescence multiplexing using spectral imaging and combinatorics (MuSIC). MuSIC consists of creating new independent probes from covalently-linked combinations of individual fluorophores, leveraging the wide palette of currently available probes with the mathematical power of combinatorics. Probe levels in a mixture can be … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The use of MuSIC probes is in principal compatible with the cyclic methods, which would expand the number of probes that can be used per round of imaging using spectral scanning microscopes. Current cyclic methods on average use 10 rounds of four-color imaging and our previous simulation studies suggested that ~25 MuSIC probes can be accurately unmixed 37 . Therefore, the use of MuSIC probes could allow 10 rounds of 25 color imaging, thus increasing multiplexing capabilities by roughly another six-fold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of MuSIC probes is in principal compatible with the cyclic methods, which would expand the number of probes that can be used per round of imaging using spectral scanning microscopes. Current cyclic methods on average use 10 rounds of four-color imaging and our previous simulation studies suggested that ~25 MuSIC probes can be accurately unmixed 37 . Therefore, the use of MuSIC probes could allow 10 rounds of 25 color imaging, thus increasing multiplexing capabilities by roughly another six-fold.…”
Section: Discussionmentioning
confidence: 99%
“…We recently developed an approach called Multiplexing using Spectral Imaging and Combinatorics (MuSIC), which leverages currently available fluorophores along with the power of combinatorics to increase the number of available probes for simultaneous staining 37 . Förster resonance energy transfer (FRET), a phenomenon whereby a higher energy fluorophore donates energy to a lower energy fluorophore 38 , is central to creating MuSIC probes with unique spectral signatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first aspect of this simulation study was to consider how to combine the individual FPs. Bimolecular FRET is common 29 , and trimolecular FRET less so, but has been reported 30 . We therefore exhaustively considered single FPs, dimers and trimers, but .…”
Section: Simulation Studies To Explore Limits and Potential Of Musicmentioning
confidence: 99%
“…Fluorophores with large ( pseudo )-Stokes shifts are highly desirable in biochemical experiments so that the label emission is at a significant longer wavelength than excitation (e.g. intracellular imaging enabling multiplexing) ( Rauf et al, 2010 ; Jeong et al, 2011 ; Shcherbakova et al, 2012 ; Holzapfel et al, 2018 ). Our new heteroleptic Zn II bis(dipyrrinato) complexes herein presented have intriguing properties to be used as fluorescent emitters for bioimaging.…”
Section: Introductionmentioning
confidence: 99%